CAUSES AND CONSEQUENCES OF THE SALINIZATION PROCESS - Sayfullayeva Sabinabonu Husniddinovna (Web of Journals Publishing, 2025)
This article analyzes the process of soil salinization, its main causes, and its ecological and economic consequences. It discusses the natural and anthropogenic factors leading to salinization, as well as the changes occurring in the physical and chemical composition of the soil. Based on the research results, recommendations are provided for preventing and reducing the degree of salinization.
Keywords: Saline soil, resources, agriculture, climate change, ecological balance.